(untitled) (International journal of artificial intelligence, 2026)
This scientific article studies the didactic possibilities of forming social adaptability competence in secondary school students as a socio-pedagogical problem. The study scientifically substantiates the need for students to adapt to the social environment, consciously accept social roles, and demonstrate constructive behavior in interpersonal relationships in the context of globalization processes and increasing information threats. The article reveals the didactic potential of reflective approaches, emotional-reflective methods, socially oriented activities, and communicative cooperation technologies in developing social adaptability competence in students. Also, the level of students' self-awareness as individuals, their attitude to their own worth, and the manifestation of adaptive behavior in various social situations are described as the main criteria for this competence. The results of the study allow for the improvement of educational activities in secondary schools and the enrichment of didactic support aimed at developing social adaptability competence.